2019
DOI: 10.1177/1465750319840778
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation in (young) SMEs

Abstract: The purpose of this article is to identify the role start-ups play in the open innovation (OI) context by reviewing the existing body of research. Since the OI literature on young ventures is nascent, a stepwise review approach is applied, using the already more evolved findings of small- and medium-sized enterprises (SMEs) in order to derive similarities or differences. The findings indicate that if empirical studies with a similar research focus are conducted, similar results are likely to be obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…This paper focuses on innovation ecosystems (IE) as they are gaining in importance and popularity in both innovation and strategic management. Furthermore, as they are crucial for development of new or young ventures and increase in the likelihood of firm survival, therefore for entrepreneurship at individual, organizational, and regional levels (Kraus et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on innovation ecosystems (IE) as they are gaining in importance and popularity in both innovation and strategic management. Furthermore, as they are crucial for development of new or young ventures and increase in the likelihood of firm survival, therefore for entrepreneurship at individual, organizational, and regional levels (Kraus et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The important role of SMEs is confirmed by many authors (Ključnikov et al, 2017;Pisar & Bilkova, 2019;Alnawas & Farha, 2020;Lewandowska & Stopa, 2018, 2019Kraus et al, 2020;Lima et al, 2020). Due to their irreplaceable role, it is necessary to create favorable conditions for their business.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Experience is necessary to develop the management capacity and skills in business and remain competitive even without technical or academic knowledge (ibid.). Vice versa, Kraus et al (2019) found that young ventures have a higher application of open innovation activities compared to large firms as it boosts their innovation performance enabling them to overcome the liability of smallness and newness.…”
Section: Financial Experiencementioning
confidence: 99%